2017
DOI: 10.1111/1365-2745.12884
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the system: How large herbivores control bottom‐up regulation of grasslands

Abstract: 3. Herbivores only had direct effects on plant variables at the dry grassland compared to direct and indirect effects on both plant and soil variables at the mesic grassland.By enhancing leaf N content at both grasslands, grazers shifted the resource controlling NAP from N in ungrazed grassland to moisture, and potentially phosphorus and/or other soil nutrients, in grazed grassland. Synthesis.These results indicate the mechanistic linkage between top-down (herbivore) and bottom-up (soil resource) control of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Moreover, enhanced leaf tissue nitrogen during the growing season (Fig. 3 B ) increases photosynthetic activity, which prolongs plant growth (23, 29). If bison grazing can both accelerate and extend plant green-up at large scale, it may alter the progression of the green wave itself across the landscape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, enhanced leaf tissue nitrogen during the growing season (Fig. 3 B ) increases photosynthetic activity, which prolongs plant growth (23, 29). If bison grazing can both accelerate and extend plant green-up at large scale, it may alter the progression of the green wave itself across the landscape.…”
Section: Resultsmentioning
confidence: 99%
“…At each site, we used a paired design of naturally grazed grassland (treatment) and exclosed grassland (control) to measure net aboveground production, grazing intensity, standing crop, and plant nutrients. We made measurements using established methods (29, 3638). For controls, we placed 3 semipermanent 9-m 2 fenced exclosures at each site.…”
Section: Methodsmentioning
confidence: 99%
“…During the experimental period, resource availability was possibly the main contributor to variations in ANPP under different grazing intensities, since some factors can be excluded such as fire history and co-evolutionary history that were not significantly affected by grazing intensity in this study. It has been reported that the dominant factors affecting resource availability in grassland ecosystems are precipitation, air temperature, nutrient availability, and soil water content (Frank et al, 2018). Previous studies have indicated that precipitation has a positive (Lezama et al, 2014; Lu et al, 2017) or neutral (Wang et al, 2012; Eldridge et al, 2016) effect on primary production in grasslands on a regional scale; in contrast, the timing of rainfall events and precipitation periods are key factors to affect ANPP on a plot scale (Knapp et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of herbivory on plant biomass should interact with nutrient availability and precipitation in grasslands (Anderson et al, 2018; Frank et al, 2018; McNaughton et al, 1989). The net effect of grazers on biomass across years at a site can alter biomass-precipitation relationships in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…If grazing enhances production by releasing the plant community from light limitation (Borer, Seabloom, et al, 2014), nutrients will have smaller effects on sensitivity when grazers are excluded. In spite of all these possible mechanisms, the generality and degree to which grazing by mammalian herbivores modulates the relationship between grassland biomass and interannual variation in precipitation has not been quantitatively evaluated (Campbell and Stafford Smith, 2000; Frank et al, 2018).…”
Section: Introductionmentioning
confidence: 99%